Neoadjuvant Treatment in Resectable Pancreatic Cancer. Is It Time for Pushing on It? - Vivarelli, Marco; Mocchegiani, Federico; Nicolini, Daniele; Vecchi, Andrea; Conte, Grazia; Dalla Bona, Enrico; Rossi, Roberta; Benedetti Cacciaguerra, Andrea (Frontiers in Oncology, 2022)
Pancreatic resection still represents the only curative option for patients affected by pancreatic ductal adenocarcinoma (PDAC) however, the association with modern chemotherapy regimens is a key factor for improving the inauspicious oncological outcome. The benefit of neoadjuvant treatment (NAT) for borderline resectable/locally-advanced PDAC has been demonstrated; this evidence raised the question whether even resectable PDAC should perform NAT rather than upfront surgery. NAT may avoid futile surgery due to undetected distant metastases or aggressive tumor biology providing more effective systemic control of the disease, which is hampered when adjuvant chemotherapy is delayed or precluded. However, recent data show controversial results regarding the efficacy and safety of NAT in resectable PDAC as compared to upfront surgery. Although several prospective studies and meta-analyses indicate better oncologic outcomes after NAT, there are some biases, such as the methodological approaches used to capture the events of interest, that could make these results hardly reproducible. For instance per-protocol studies, considering only the postoperative outcomes, tend to overestimate the performance of NAT by excluding patients who will be never suitable for surgery due to development of chemotoxicity or tumor progression. To draw reliable conclusions, the studies should capture the events of interest of both strategies (NAT/upfront surgery) from the time of allocation to a specific treatment, in an intention-to-treat fashion. This critical review aims to highlight the current literature data concerning the use of NAT in resectable PDAC, summarizing the results of high-quality studies and focusing on the methodological issues of the recent evidences.